Efeitos da idade da matriz e do tamanho do ovo sobre os pesos dos componentes dos ovos, do pinto, do saco vitelino, a uniformidade, o desempenho e o rendimento de abate do frango de corte - Julia Sampaio Rodrigues Rocha (2007)
To evaluate the effects of broiler breeder age and egg size on egg components weight, hatch chick and yolk sac weights, uniformity, performance and meat yields of broiler chickens, an experiment was conducted in two phases. In first trial of experimental phase 1, the three treatments were: M31, M38 e M43 (eggs collected from flocks of 31, 38 and 43 wk old) to evaluate the effects of broiler breeder age on egg weight uniformity and yolk, albumen and shell percentages. It was a completely randomized design, with 360 replicates for egg weight uniformity and 180 replicates for egg components percentages. In second trial of experimental phase 1, eggs produced by three broiler breeder flocks (31, 38 e 43 wk old) were divided in six treatments: by broiler breeder age (O31 – eggs from broiler breeder of 31 wk old weighting 52 to 72g, O38 – eggs from broiler breeder of 38 wk old weighting 52 to 72g, and O43 – eggs from broiler breeder of 43 wk old weighting 52 to 72g) and by egg sizes (OG – large eggs weighting 66 to 72g, OM – medium eggs weighting 58 to 65g, and OP – small eggs weighting 52 to 57g). This second trial was realized to evaluate the effects of broiler breeder age and egg size on hatchability, embryonic mortality and relationship between hatch chick and yolk sac weights. It was a completely randomized design, with 16 replicates for hatchability and embryonic mortality, 48 replicates for relationship between hatch chick and egg weights, and 32 replicates for relationship between hatch chick and yolk sac weights. In experimental phase 2, 1680 broiler chickens were utilized, being 140 males and 140 females born from each of six treatments of second trial in experimental phase 1, to evaluate the uniformity, performance, and meat yields of broiler chickens. It was a completely randomized design, in a 6 x 2 factorial (six treatments – three broiler breeder ages and three egg sizes x two sexes) with four replicates of 35 birds each. The chicks were raised from one to 44 days and the slaughter was realized when they were 45 days old. Eggs produced by broiler breeders of 31 wk old had egg and yolk weights more uniform than the eggs collected from flock of 43 wk old. The hatchability of large eggs was the worst and embryonic mortality was increased after 15 days of incubation in these eggs. The large eggs produced heavier hatch chicks with superior absolute and relative yolk sac weights. Hatch chick is determined by egg weight, being 68,3% of egg weight, independent on broiler breeder age and egg size. Sorting eggs by weight prior to incubation was not efficient to keep the better broiler chickens uniformity until 44 days of age. There is a significant positive relationship between seven-days-old weights and broiler weights at slaughter age (44 dias), except in chickens from flock of 31 wk old. Broiler chickens weights at 44 days old are more affected by weight gain capacity than broiler breeder age and egg size. Feed conversion ration, viability and meat yields are not affected by broiler breeder age or egg size.